Interleukin-6 production by human monocytes stimulated with Cryptococcus neoformans components. - Delfino, D (1997)
In order to ascertain if Cryptococcus neoformans components can induce interleukin-6 (IL-6) production, we stimulated human whole blood with purified capsular products. Their potencies in stimulating IL-6 release were mannoproteins > galactoxylomannan = glucuronoxylomannan > alpha(1-3)glucan. IL-6 production was tumor necrosis factor alpha independent and required the presence of monocytes and plasma. Since IL-6 can stimulate replication of the human immunodeficiency virus in monocytic cells, these findings may be clinically relevant.